Implementing EVM-Based Self-Sovereign Identity to Meet European Digital Identity Compliance for Decentralized Finance - Košubienė, Gintarė; Masteika, Saulius (Vilnius University Open Series, 2025)
This paper presents an implementation of a Self-Sovereign Identity (SSI) framework using Ethereum-based standards to meet the technical requirements of the European Digital Identity (EUDI) Architecture Reference Framework (ARF). By leveraging ERC-734/ERC-735 standards, the proposed eSSI system enables decentralized key management, verifiable claims, and onchain auditability. A case study on the Sepolia testnet demonstrates functional alignment with EUDI goals, while highlighting the need for enhanced privacy mechanisms such as zero-knowledge proofs for full compliance.